Circulation of HAdV-41 with diverse genome types and recombination in acute gastroenteritis among children in Shanghai - Peng Li (Nature Portfolio, 2017)
Abstract Human adenovirus F (HAdV-F) is one of the major causative species detected in acute gastroenteritis in children worldwide. HAdV-F is composed of serotypes 40 and 41. Most studies have reported the prevalence of HAdV-41 and focused on its epidemiologic characteristics. In this study, seventeen samples were identified as HAdV-41 out of 273 fecal specimens from children with acute diarrhea in Shanghai. Five isolates were isolated and subjected to whole genome sequencing and analysis to characterize the genetic variation and evolution. Full genome analysis revealed low genetic variation (99.07–99.92% identity) among the isolates, and InDels are observed in the E2A gene and the hexon gene compared to the reference strain NIVD103. Phylogenetic analysis showed that all isolates mainly formed two genome-type clusters but with incongruence in the trees of whole genomes and individual genes. The recombination breakpoints of the five isolates were inferred by the Recombination Detection Program (RDP) and varied in the number and location of the recombination events, indicating different evolution origins. Overall, our study highlights the genetic diversity of HAdV-41 isolates circulating in Shanghai, which may have evolved from inter-strain recombination.